Model for PKI interoperability in Serbia - Prodanović, Radomir I.; Vulić, Ivan B. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The increasing use of electronic services that use electronic certificates and the increasing implementation of public key infrastructures require their interconnection and interoperability. In this paper, the authors analyze the models for interoperability between various PKI domains and their possible application in achieving interoperability of the public key infrastructures in the Republic of Serbia. The implementation of the interoperability of the existing models is discussed from the following aspects: scalability, processing of certification paths, implementing policies, the points of failure and the possibilities of re-establishing trust. We proposed a conceptual model based on the Bridge Certification Authority trust model. This model can provide the establishment of the interoperability of both the existing and new national PKI domains, their interconnection as well as their connection with foreign PKI domains. The model was extended with the Validation Authority that provides more efficient processing of the certification path.
Keywords: certificate; PKI systems; Domains; Interoperability; models; infrastructure